Successful treatment of classic kaposi sarcoma with long-pulse neodymium-doped yttrium aluminum garnet laser: A preliminary study - Özdemir, Mustafa; Balevi, Ali (Lippincott Williams & Wilkins, 2017)
BACKGROUND Kaposi sarcoma (KS) is a systemic disease that can present with cutaneous lesions with or without internal involvement, mostly caused by infection with human herpesvirus-8. The treatment options include surgical excision, cryotherapy, radiotherapy, intralesional chemotherapy, laser, and elastic stockings for the prevention of lymphedema. OBJECTIVE This article presents 7 cases with classic KS treated with the long-pulse neodymium: yttriumaluminum- garnet (Nd:YAG) laser. METHODS Forty-nine lesions of 7 KS patients (5 stage 1, 2 stage 2A) were treated with Nd: YAG laser with a spot size of 4 to 6 mm and a fluence of 180 J/cm(2) increased by 10 J/cm(2) in the neighboring area to a maximum of 260 J/cm(2). The pulse sequencing was 1.5, and delay time was 5 milliseconds. Sessions were continued at 4-week intervals for 2 to 4 sessions. RESULTS All patients exhibited clinical and histological improvement. One session was sufficient for small lesions, whereas coalescing and multicentric lesions required up to 4 sessions. All the lesions healed in 2 to 4 weeks, with the only complication being mild atrophic scars. CONCLUSION With the advantage of penetrating into deeper sites than other lasers, long-pulse Nd:YAG is an efficient and safe local treatment alternative especially for papulonodular and deeper lesions located on bony structures.
WOS: 000398047200007
PubMed ID: 28157730
Keywords: Neodymium-Doped Yttrium Aluminum; Classic Kaposi Sarcoma; Successful Treatment